Effects of Audio-Guided Adaptive Gymnastics on Physical Fitness among Students with Visual Impairment: A Controlled School-Based Intervention - Gita Nurgaya Br Tarigan; Ramadan Ramadan; Putri Lagenda Wulandari (INSPIRETECH GLOBAL INSIGHT, 2026)
Introduction. Students with visual impairment are consistently under-represented in school physical activity because mainstream physical education is transmitted through visual demonstration, visual environmental orientation, and visually mediated corrective feedback. The resulting instructional inaccessibility is associated with reduced motor competence, lower habitual physical activity, and diminished health-related physical fitness. Audio-guided adaptive gymnastics has been proposed as an accessible alternative in which visual demonstration is systematically replaced by standardised verbal movement description, rhythmic temporal cues, spatially anchored sound, and immediate auditory feedback. Purpose. The study examined the effects of an eight-week audio-guided adaptive gymnastics programme on health-related physical fitness among students with visual impairment enrolled at UPT SLB-E Negeri PTP Sumatera Utara, Indonesia. Materials and methods. A controlled pretest–posttest experimental design was applied. Twenty-four students with visual impairment aged 12–17 years were allocated to an audio-guided adaptive gymnastics group (n = 12) or to a control group receiving the regular adapted physical education programme (n = 12). The intervention was delivered three times weekly for eight weeks (24 sessions, ≈40 min per session) and comprised auditory orientation, rhythmic locomotor work, muscular endurance exercise, dynamic balance tasks, flexibility work, and audio-guided relaxation. Physical fitness was assessed using the six-minute walk/run test, the 30-second sit-to-stand test, the 30-second curl-up test, the sit-and-reach test, and the single-leg balance test, combined into a standardised composite score. Data were analysed with 2 × 2 mixed-design analysis of variance, analysis of covariance, partial eta squared, Cohen's d, and 95% confidence intervals. Results. A significant group × time interaction was observed for the composite physical fitness score, F(1, 22) = 25.84, p < .001, partial η² = .540. The intervention group improved more than the control group in cardiorespiratory endurance, lower-body muscular endurance, abdominal muscular endurance, flexibility, and static postural balance. The adjusted between-group difference at posttest was 11.71 points, 95% CI [6.29, 17.13], with a large standardised effect, d = 1.42. Significant interactions were also obtained for all secondary outcomes (p ≤ .002; d = 0.91–1.42). Adherence was 94.2% and no serious adverse events were recorded. Conclusions. Audio-guided adaptive gymnastics is a feasible, low-cost, and potentially effective strategy for improving multiple components of health-related physical fitness in school-aged students with visual impairment. Standardised auditory instruction, predictable rhythmic structure, and immediate accessible feedback may enhance movement accuracy, autonomy, confidence, and sustained participation. Larger multicentre randomised trials with device-based physical activity monitoring and extended follow-up are warranted.